The Application of Loose Part Media in Improving Numeracy Literacy of Children Aged 5-6 Years - Nisa, Fadhilah Sayyidatun; Hasmawaty, Hasmawaty; Instisari, Instisari; Romba, Sri Sufliati (Universitas Negeri Makassar, 2025)
This research aims to describe the application of loose part media in improving numeracy literacy skills in children aged 5–6 years at TK Bukit Permai 2, Gowa Regency. This research uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, which includes planning, implementation, observation, and reflection. The research subjects were 15 children from group B aged 5–6 years. Data collection techniques used observation and documentation, with data analysis carried out qualitatively and quantitatively. The results showed that the use of loose part media significantly improved children's ability to recognize number symbols, form letters and numbers, and solve simple arithmetic operations. Therefore, loose part media is effectively used to develop early childhood numeracy literacy. The findings contribute valuable insights to curriculum development and emphasize the importance of play-based, meaningful learning in preparing children for future academic success